Eikelboom filamentous morphotypes 0675 and 0041 embrace members of the Chloroflexi: resolving their phylogeny, and design of fluorescence in situ hybridisation probes for their identification. Issue 10 (6th September 2017) - Speirs, Lachlan B. M.; Dyson, Zoe A.; Tucci, Joseph; Seviour, R. J.
Abstract: Although the phylogeny of many of the filamentous bacteria responsible for bulking in activated sludge plants is now known, and fluorescence in situ hybridisation (FISH) probes have been designed for their in situ identification, there are some noticeable exceptions. This study reports the identification of the Eikelboom morphotypes 0041 and 0675. Because these morphotypes differ only in their filament diameters, they are often considered together in surveys based on microscopic identifications. Here we show that they are phylogenetically distinct, and so should be viewed no longer as morphological variants of a single population. Amplicon sequencing data of Australian EBPR plant biomass containing types 0041 and 0675, and phylogenetic analysis have revealed that both, like many other bulking filament morphotypes, are members of the phylum Chloroflexi and probably representatives of two different genera. FISH probes are described here targeting each. Surveys carried out on Australian activated sludge plants suggest that type 0675 occurs more in plants designed to remove phosphorus, while type 0041 shows no such preference, and was seen in biomass samples from a wide range of plant configurations. Abstract : Newly identified bulking filamentous bacteria are found to be members of the Chloroflexi, and common in Australian activated sludge systems.